3rd International Conference & Exhibition on Semiotics and Visual Communication - Panayides, Angelos (My University, 2026)
Invited Designer Participated with the poster “What’s on your mind?” The conference accommodated the work of 21 designers-illustrators from Cyprus and abroad who were invited to design a poster under the theme of ‘explosion[s]: the global logo’, and come up with a ‘brand-logo’ for the explosion [as the predominant ‘logo’ of the 21st Century].